DISMANTLING THE STEREOTYPES OF ISLAM, ARAB, AND MUSLIM WOMEN IN THE VISUAL AND PRINT MEDIA OF THE WESTERN WORLD - Amz, Tsuroyya (Jurnal Kajian Komunikasi, 2014)
Reel Bad Arabs movie indicated that the 9/11 attacks provided a basis for bipolarizing the Western and theMuslims worlds. As a result, a lot of misconceptions of the Muslim world presented in the media embodya rigid concept, comparing and contrasting Western and Islamic/Arabic values in which Western values arefavored after the 9/11 attack. Grounded in Reel Bad Arabs and several studies of print media about Islamrepresentations, this paper examined the concepts of Islamophobia focusing on stereotypes of Islam and Arabwomen as well as the relationship of modernity, capitalism, and Islam as they are perceived by the Muslimworld. Employing the agenda-setting theory and basic concepts of Islamophobia, this paper analyzed theselected texts in-depth qualitatively. Correspondingly, previous researches were used to expand the accountof the relationship between Islam and the Western media. The analysis claimed that selected print and visualmedia depict Islam unfavorably leading to a misconception of Islam in the Western world. In fact, stereotypesof Islam proved to be more salient as promoted by the Western media. However, the Muslim media attemptedto challenge this by producing several media products such as Kalam Nawaem to show a more âbalancedâIslam.Keywords: Stereotypes, media, Muslim, Islamophobia, IslamDOI: 10.24198/jkk.vol2n2.5